Service Quality Interior Caffe CV. Apik Kayu Banjardowo Jombang Village - Ahmad Jainuri; Suci Prihatiningtyas; Mar'atul Fahimah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to determine the effect of service quality (reliability, responsiveness, assurance, empathy, physical evidence) on consumer satisfaction at CV. Kayu Apik and the most dominant variables affect consumer satisfaction CV. Apik jombang wood. This research uses a qualitative approach with the type of case study research. There are two sources of data in this research, namely primary and secondary data. The data collection used by the author in this research is purposive sampling. Data collection techniques were carried out by interview, observation, and documentation. In this study, the research instruments were: the researcher himself as the main instrument, interview guidelines, and field notes. The data analysis technique used is descriptive analysis of the results of the interview, the researcher will describe and analyze based on the theoretical framework used in this study. The data validity technique used by the researcher is triangulation. Triangulation is a technique of checking the validity of data that utilizes something other than the data for checking purposes or as a comparison against the data. The results show that the effect of service quality (trustworthiness, responsiveness, assurance, empathy, physical evidence) on customer satisfaction at CV. Kayu Apik is very good and the most dominant variable influencing consumer satisfaction CV. Kayu Apik Jombang is the dimension of Reability and Assurance.